A partial C-4 photosynthetic biochemical pathway in rice - Lin, HsiangChun; Arrivault, Stéphanie; Coe, Robert A.; Karki, Shanta; Covshoff, Sarah; Bagunu, Efren; Lunn, John E.; Stitt, Mark; Furbank, Robert T.; Hibberd, Julian M.; Quick, William Paul (Frontiers Media, 2020)
Introduction of a C4 photosynthetic pathway into C3 rice (Oryza sativa) requires installation of a biochemical pump that concentrates CO2 at the site of carboxylation in modified bundle sheath cells. To investigate the feasibility of this, we generated a quadruple line that simultaneously accumulates four of the core C4 photosynthetic enzymes from the NADP-malic enzyme subtype, phosphoenolpyruvate carboxylase (ZmPEPC), NADP-malate dehydrogenase (ZmNADP-MDH), NADP-malic enzyme (ZmNADP-ME), and pyruvate phosphate dikinase (ZmPPDK). This led to enhanced enzyme activity and mild phenotypic perturbations but was largely neutral in its effects on photosynthetic rate. Measurements of the flux of 13CO2 through photosynthetic metabolism revealed a significant increase in the incorporation of 13C into malate, consistent with increased fixation of 13CO2 via PEP carboxylase in lines expressing the maize PEPC enzyme. However, there was no significant differences in labeling of 3-phosphoglycerate (3PGA) indicating that there was no carbon flux through NADP-ME into the Calvin-Benson cycle. There was also no significant difference in labeling of phosphoenolpyruvate (PEP) indicating that there was no carbon flux through PPDK. Crossing the quadruple line with a line with reduced glycine decarboxylase H-protein (OsGDCH) abundance led to a photosynthetic phenotype characteristic of the reduced OsGDCH line and higher labeling of malate, aspartate and citrate than in the quintuple line. There was evidence of 13C labeling of aspartate indicating 13CO2 fixation into oxaloacetate by PEPC and conversion to aspartate by the endogenous aspartate aminotransferase activity. While Kranz anatomy or other anatomical modifications have not yet been installed in these plants to enable a fully functional C4 cycle, these results demonstrate for the first-time a partial flux through the carboxylation phase of NADP-ME C4 metabolism in transgenic rice containing two of the key metabolic steps in the C4 pathway.